Different therapy options protecting microvasculature after experimental cerebral ischaemia and reperfusion - Burggraf, Dorothe; Vosko, Milan R.; Schubert, Marion; Stassen, Jean-Marie; Hamann, Gerhard F. (Thrombosis and Haemostasis, 2010)
Recombinant tissue plasminogen activator (rt-PA) is successfully used in human stroke, but often shows serious drawbacks. To find an alternative, we hypothesised that the novel thrombolytic microplasmin would have fewer adverse effects on haemoglobin extravasation and microvascular damage compared with the effects of rt-PA and tenecteplase (TNK). A constant period of ischaemia (3 hours) was induced in a rat suture model followed by reperfusion (24 hours). Mikroplasmin (10 mg/kg), TNK (5 mg/kg), rt-PA (9 mg/kg) and saline (control), were administered. The volume of the ischaemic lesion was calculated, the loss of collagen type IV and the extravasation of haemoglobin were quantified by Western blotting. The matrix-metalloproteinases 2 and 9 (MMP-2/-9) were quantified by zymography and their endogenous tissue inhibitors (TIMPs) were analysed by reverse zymography. Microplasmin treatment caused the lowest volume of the ischaemic lesion (51.0 ± 22.6 mm3) compared with control (167.3 ± 13.1 mm3; p<0.05). The content of col-lagen type IV was significantly increased and haemoglobin extravasation reduced (154 ± 24%; p<0.05) compared with control (442 ± 124%); MMP-2/-9 and the corresponding TIMPs remained unchanged. In comparison, TNK did not significantly reduce basal lamina damage and caused the highest extravasation. MMP-2/-9 were severely increased after TNK treatment (p<0.05). Thus, the balance between MMPs and TIMPs was shifted toward the inhibitory side with TNK. Microplasmin had a protective effect on the microvascular basal lamina and blood-brain barrier, whereas TNK was significantly disadvantageous from the viewpoint of ischaemic damage. Microplasmin also appears to be safer than other PAs in terms of damage to the microvasculature associated with thrombolytic therapy of ischaemic stroke.
Keywords: Cerebral ischaemia; microplasmin; MMPs; plasminogen activator; rat; rt-PA; tenecteplase